Thin-film composite nanofiltration membrane: a study on the curing time and its performance evaluation - Mah, K. H. (2020)
Xylose is the raw material for xylitol production which can be obtained through hydrolysis of agriculture waste. However, the presence of glucose in hydrolysate interferes in the process. Thin-film composite membrane developed through interfacial polymerization (IP) can be tailored for xylose separation through manipulation preparation conditions. In this study, the impact of curing conditions, specifically curing time was investigated on xylose separation. The thin-film composite (TFC) membrane was formed from IP between triethanolamine (TEOA) and tri-mesoyl chloride (TMC) on polyethersulfone support membrane. Attenuated Total Reflection Fourier Transform Infrared (ATR-FTIR) spectroscopy and contact angle measurement were performed to investigate the formation of thin-film. Evaluation of membrane performances, namely pure water flux, permeation flux, and xylose separation factor was used to evaluate the TFC membrane cured at a different time (2, 5, 10, 15, and 20 minutes). A decrease in flux was observed when prolonged the curing time for TFC membrane. A minimum of 5 minutes curing time would be needed for the organic solvent to be evaporated from the membrane at 60 oC, but 15 minute curing time would have better xylose separation.